Measurements of Sound Velocity of Liquid Fe‐11.8 wt % S up to 211.4 GPa and 6, 150 K. Issue 6 (15th June 2018) - Huang, H.; Leng, C.; Wang, Q.; Yang, G.; Hu, X.; Wu, Y.; Liu, X.; Fei, Y.
Abstract: Using the dynamic compression technique, the sound velocities of Fe‐11.8 wt % S were measured up to 211.4 (4.5) GPa and 6, 150 K. Discontinuities both in shock velocity and sound velocity indicate that Fe‐11.8 wt % S completely melts at a pressure of 111.3 (2.3) GPa. By the energy conservation law, the calculated liquidus temperature is about 2, 500 (300) K. Extrapolated to the inner‐core boundary based on the Lindeman law, the liquidus temperature of Fe‐11.8 wt % S is 4, 300 (300) K. We developed a thermodynamic model fit to the experimental data, which allows calculation of the densities and sound velocities of liquid Fe‐S under core conditions. For liquid Fe‐11.8 wt % S and Fe‐10 wt % S, good agreement was achieved between the extrapolations using our model and experimental measurements at very low pressure. Under the conditions of the outer core, the densities and bulk sound velocities of Fe‐10 wt % S provide a good fit to observed seismic profiles of Earth's core. Our results imply that an upper limit of 10 wt % S content in Earth's core satisfies the geophysical constraints. Simultaneously considering other geochemical constraints, the outer core may contain about 6 wt % sulfur and 4 wt % silicon. Plain Language Summary: Sulfur (S) has been suggested as a key light element in Earth's outer core, but there are considerable controversies on its amount. To constrain the concentrations of S in the outer core, the sound velocities of Fe‐11.8 wt % S were measured up to 211.4 (4.5) GPa using the dynamic compression technique. The discontinuity in sound velocity indicates that Fe‐11.8 wt % S completely melts at 111.3 (2.3) GPa and temperature about 2, 500 (300) K. Under outer core conditions, the density and bulk sound velocity of Fe‐10 wt % S both match the observed seismic profiles. Our results indicate that the amount of S in Earth's outer core is no more than 10 wt % assuming S is the sole light element. On the basis of geochemical constraints, we infer the outer core might contain about 6 wt % S and 4 wt % Si. Key Points: Sound velocities of liquid Fe‐11.8 wt % S were measured up to 211.4 GPa along Hugoniot Fe‐11.8 wt % S completely melts at 111.3 (2.3) GPa and 2, 500 (300) K The outer core may contain about 6 wt % sulfur and 4 wt % silicon